Architect Aesthetic Concept in WYAH Art and Creative Space Cafe Building Ubud, Bali - Widyawati, Anak Agung Ayu Pratiwi; Rachmawati, Murni; Novianto, Didit (ASTONJADRO, 2023)
The concept of architectural aesthetics is closely related to the architect who designed it. Architectural works of art today do not only consider the function and robustness of the structure, but also the aesthetic aspects. Current architectural developments show the trend of developing cafe buildings with unique designs that are owned as an attraction, one of which is the WYAH Art and Creative Space cafe building. This affects architects and is expected to be able to create buildings with new innovations that are unique and aesthetically attractive. This study aims to identify the aesthetic concepts applied by architects in WYAH cafe buildings. Based on the research objectives, this study uses a qualitative strategy with a phenomenology approach. The analysis technique used is content analysis and interpretive architectural criticism. The result obtained is that the aesthetic concept applied by the architect in the process of designing the WYAH cafe building adopts the surrounding nature potentials (utilizing land conditions). The implication is that this building becomes an attraction and attracts the interest of many visitors, so it can be concluded that the architect's aesthetic concept is an important value in the process of designing architectural works.